Adaptive Deployment Scheme and Multi-path Routing Protocol for WMSNs - Enyan Sun; Xuanjing Shen; Haipeng Chen; Chuanyun Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Multi-path routing protocols have many advantages in wireless multimedia sensor networks. To succeed in setting up multiple paths in the wireless multimedia sensor network, the Adaptive Deployment Scheme of sensor Nodes which is based upon multi-path routing protocol (ADSN) is proposed in the paper. ADSN deploys the sensor nodes on the basis of the number of paths, camera nodes’ positions and the sink’s position etc. Compared to the uniform deployment scheme, ADSN can save 67% sensor nodes when setting up multiple paths. And it can avoid the hotspot area in the vicinity of the sink. Energy Equalization Multi-path Routing protocol (EEMR) can consume the energy of sensor nodes more evenly and extends the network lifetime compared to TPGF. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3820